Bailey's billions - Cain, Dean.; Holden, Laurie; Tilly, Jennifer, 1958-; Echo Bridge Home Entertainment (Firm) (LaCrosse, WI : Echo Bridge Home Entertainment, 2006)
Bailey is a lucky golden retriever who has just become rich by inheriting his owner's money. One day, Bailey disappears and it is up to a 12-year-old girl and the other dogs to find him.
Title from container.
Originally released as a motion picture in 2005.
Dean Cain, Laurie Holden, Jennifer Tilly, Tim Curry, Max Baker.
Voice of Bailey: Jon Lovitz.
MPAA rating: G.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital.
Keywords: Dog rescue -- Drama; Golden retriever -- Drama; Comedy -- Feature